2022
DOI: 10.5009/gnl220218
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of 14-Day Tegoprazan- versus Rabeprazole-Based Triple Therapy for Eradication of Helicobacter pylori: A Real-World Evidence Study

Abstract: Background/Aims: Tegoprazan, a new, fast, and strong potassium-competitive acid blocker, has been approved for the treatment of gastric acid-related diseases in Korea. However, realworld clinical data regarding this drug are scarce. We aimed to compare the Helicobacter pylori eradication rates of tegoprazan-and rabeprazole-based triple therapy. Methods:We retrospectively reviewed data from patients who received first-line treatment for H. pylori infection using tegoprazan-or rabeprazole-based triple therapy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Although this study did not include an esomeprazole-based triplet regimen, we could infer the impact of sodium bicarbonate on H. pylori eradication therapy by reviewing the results of previous studies. In an earlier multicenter randomized controlled trial and our real-world study, tegoprazan-based triple therapy showed an eradication rate similar to that of PPI-based triple therapy ( 9 , 10 ). Although P-CAB typically exerts a rapid and potent acid-inhibitory effect, the dosage of P-CAB may be critical for achieving a high eradication rate.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Although this study did not include an esomeprazole-based triplet regimen, we could infer the impact of sodium bicarbonate on H. pylori eradication therapy by reviewing the results of previous studies. In an earlier multicenter randomized controlled trial and our real-world study, tegoprazan-based triple therapy showed an eradication rate similar to that of PPI-based triple therapy ( 9 , 10 ). Although P-CAB typically exerts a rapid and potent acid-inhibitory effect, the dosage of P-CAB may be critical for achieving a high eradication rate.…”
Section: Discussionsupporting
confidence: 57%
“…However, diarrhea was more common in patients receiving tegoprazan-based quadruple therapy than in those receiving rabeprazole-based quadruple therapy. Considering the high risk of diarrhea with bismuth-containing quadruple therapy ( 10 ), the incidence of diarrhea with second-line rabeprazole-based quadruple therapy in this study (4.2%) was relatively low. Although the underlying cause for this inconsistency remains unclear, it could be explained by the relatively high proportion of patients who received first-line esomeprazole/sodium bicarbonate–based triple therapy in the second-line rabeprazole-based quadruple therapy group.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Eradicating H. pylori is of utmost significance, serving as the primary treatment for low-grade G-MALT, mitigating the recurrence of peptic ulcers, and lowering the risk of gastric adenocarcinoma in high-risk populations[ 10 - 12 ]. This critical therapeutic intervention not only addresses immediate health concerns but also plays a pivotal role in preventing more severe and potentially life-threatening conditions associated with H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%